Performance and economic analysis of a solar membrane distillation pilot plant under various operating conditions - Choi, Jihyeok; Cho, Jinsoo; Shin, Jaewon; Cha, Hoyoung; Jung, Jinho; Song, Kyung Guen (Pergamon Press Ltd., 2022)
Although membrane distillation (MD) is a promising desalination process, its use is limited because it requires a large amount of thermal energy. To reduce the thermal energy consumption during MD, studies combining various renewable energy sources (e.g., solar, geothermal, and waste heat) are currently being conducted. Therefore, pilot plant experiments combining solar energy with an MD system were conducted. In particular, a module that could be changed into different MD configurations, including direct contact MD (DCMD) and air gap MD (AGMD), was reviewed. The performance of the pilot plant was analyzed for each configuration under various operating conditions and according to onsite weather conditions. Because DCMD can obtain a 43% higher water flux than can AGMD, a long-term DCMD test was conducted to achieve a high water flux. The specific energy consumption (SEC) and gained output ratio (GOR) were compared in the presence and absence of solar energy. A 30% decrease in the SEC and 17% increase in the GOR were observed for the sunny days compared with when no solar energy was used. These results indicate that combining the MD with solar energy can improve its performance during long-term operation. In addition, the cost per unit volume of product water was estimated based on the designed solar MD pilot plant.